Treatment of Dental Pulp Injuries with the Ultrasound Endoactivator - Toʻlqin oʻgʻli, Elnazarov Azamat; Munisovna, Khaydarova Durdona (American Journal of Biomedicine and Pharmacy, 2025)
Currently, in the biological treatment of dental pulp diseases, agents with bactericidal effects - antibiotics, antiseptics and anesthetics - are used in combination with calcium hydroxide (HC) [3,5]. Calcium hydroxide-based preparations have been effectively used in dental practice for more than 130 years. Its highly alkaline environment (pH ≈ 12) inhibits the vital activity of microorganisms and reduces inflammatory processes in the pulp and periapical tissues. At the same time, calcium hydroxide stimulates remineralization and the formation of reparative dentin in dental tissues, that is, it has a dentinotropic effect [2,6,9,14]. Several studies have demonstrated the potent antimicrobial activity of calcium hydroxide against cariogenic microorganisms, particularly Streptococcus mutans , Lactobacillus acidophilus , and Enterococcus faecalis strains [1,4,8,11]. As a result, calcium hydroxide has been accepted as one of the main biological agents for controlling microflora in endodontic procedures. However, calcium hydroxide has some drawbacks. It does not adhere well to dentin walls and can create microinterface gaps, which can lead to re-introduction of bacteria and their toxins [7,13]. Therefore, we aimed to study the antibacterial effect of calcium copper hydroxide and its advantages.